Dissolved iron and iron isotopes in the southeastern Pacific Ocean. Issue 10 (5th October 2016) - Fitzsimmons, Jessica N.; Conway, Tim M.; Lee, Jong‐Mi; Kayser, Richard; Thyng, Kristen M.; John, Seth G.; Boyle, Edward A.
Abstract: The Southeast Pacific Ocean is a severely understudied yet dynamic region for trace metals such as iron, since it experiences steep redox and productivity gradients in upper waters and strong hydrothermal iron inputs to deep waters. In this study, we report the dissolved iron (dFe) distribution from seven stations and Fe isotope ratios (δ 56 Fe) from three of these stations across a near‐zonal transect from 20 to 27°S. We found elevated dFe concentrations associated with the oxygen‐deficient zone (ODZ), with light δ 56 Fe implicating porewater fluxes of reduced Fe. However, temporal dFe variability and rapid δ 56 Fe shifts with depth suggest gradients in ODZ Fe source and/or redox processes vary over short‐depth/spatial scales. The dFe concentrations decreased rapidly offshore, and in the upper ocean dFe was controlled by biological processes, resulting in an Fe:C ratio of 4.2 µmol/mol. Calculated vertical diffusive Fe fluxes were greater than published dust inputs to surface waters, but both were orders of magnitude lower than horizontal diffusive fluxes, which dominate dFe delivery to the gyre. The δ 56 Fe data in the deep sea showed evidence for a −0.2‰ Antarctic Intermediate Water end‐member and a heavy δ 56 Fe of +0.55‰ for distally transported hydrothermal dissolved Fe from the East Pacific Rise. These heavy δ 56 Fe values were contrasted with the near‐crustal δ 56 Fe recorded in the hydrothermal plume reaching Station ALOHA in the North Pacific. The heavy hydrothermal δ 56 Fe precludes a nanopyrite composition of hydrothermal dFe and instead suggests the presence of oxides or, more likely, binding of hydrothermal dFe by organic ligands in the distal plume. Key Points: Elevated dFe in the Chilean ODZ is derived from porewater but is redox cycled on short spatiotemporal scales Vanishingly low dFe in the surface gyre is dominated by horizontal fluxes and less by dust inputs Hydrothermal‐derived deep dFe is isotopically heavy in the South Pacific, while it has near‐crustal isotope composition at Station ALOHA